2021
DOI: 10.1093/g3journal/jkab025
|View full text |Cite
|
Sign up to set email alerts
|

Nested association mapping reveals the genetic architecture of spike emergence and anthesis timing in intermediate wheatgrass

Abstract: Intermediate wheatgrass (Thinopyrum intermedium) is an outcrossing, cool season grass species currently undergoing direct domestication as a perennial grain crop. Though many traits are selection targets, understanding the genetic architecture of those important for local adaptation may accelerate the domestication process. Nested association mapping (NAM) has proven useful in dissecting the genetic control of agronomic traits many crop species, but its utility in primarily outcrossing, perennial species has y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…We previously described a 1,168-individual-F 1 nested association mapping (NAM) population of IWG that was developed from 11 phenotypically divergent parents from Cycle 2 of the University of Minnesota breeding program (Yu et al, 2008;Altendorf et al, 2021). In this previous work, we used flowering time traits as proof of concept and demonstrated that this population and the described methods were effective at identifying both new and previously detected quantitative trait loci (QTL) that align closely with wellcharacterized flowering time orthologs from barley, notably Ppd-H1, Constans, and PhyB (Altendorf et al, 2021). Here, we map three traits that are major targets of selection in IWG breeding: brittle rachis, floret shattering, and threshability.…”
Section: Core Ideasmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously described a 1,168-individual-F 1 nested association mapping (NAM) population of IWG that was developed from 11 phenotypically divergent parents from Cycle 2 of the University of Minnesota breeding program (Yu et al, 2008;Altendorf et al, 2021). In this previous work, we used flowering time traits as proof of concept and demonstrated that this population and the described methods were effective at identifying both new and previously detected quantitative trait loci (QTL) that align closely with wellcharacterized flowering time orthologs from barley, notably Ppd-H1, Constans, and PhyB (Altendorf et al, 2021). Here, we map three traits that are major targets of selection in IWG breeding: brittle rachis, floret shattering, and threshability.…”
Section: Core Ideasmentioning
confidence: 99%
“…Parental selection and methods for developing the IWG NAM were previously described in detail in Altendorf et al (2021). Briefly, 10 phenotypically diverse donor genets were identified from Cycle 2 of the UMN breeding program and crossed to WGN59, which is a low-shattering genet, in a reciprocal manner.…”
Section: Population Development and Establishmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, decreased sequencing cost has resulted in a wealth of genomic information for crop improvement including genetic maps (Kantarski et al 2016), a draft genome sequence (https://phytozomenext.jgi.doe.gov/info/Tintermedium_v2_1). These genomics resources have enabled genomewide association studies (GWAS) for agronomic traits including seed size (Zhang et al 2017;Larson et al 2019), flowering time (Altendorf et al 2021b), and grain yield components (Bajgain et al 2019;Larson et al 2019) that can be used to better understand and guide IWG breeding.…”
Section: Introductionmentioning
confidence: 99%